INFLAMMATORY MECHANISMS IN COLORECTAL CANCER: THE ROLE OF CYTOKINES AND DIETARY INFLAMMATORY INDEX - A REVIEW - Sarajlić, Lana; Mekić Abazović , Alma; Hodžić, Edin; Gavrić, Igor; Bajramagić, Salem; Mehić, Amina; Halilović, Emsad; Firdus, Nedžad (Sanamed, 2025)
Colorectal cancer is one of the most common malignant tumors, with numerous studies highlighting the role of inflammation in its onset and progression. Cytokines such as IL-6 and TNF-α play a crucial role in sustaining inflammation, contributing to the malignant transformation of cells. The dietary inflammatory index, which reflects the intake of pro-inflammatory nutrients, is associated with an increased risk of developing colorectal cancer. Serum cytokine concentrations may serve as biomarkers for risk assessment, while dietary modifications aimed at reducing inflammation can significantly impact both prevention and therapy. This knowledge opens possibilities for a personalized approach to the treatment and prevention of colorectal cancer.
Keywords: Colorectal Neoplasms; Inflammation; Cytokines; Feeding Behavior